Skeletal Muscle Mass Measurement Using Cone-Beam Computed Tomography in Patients With Head and Neck Cancer - Huang, Wei; Tan, Peixin; Zhang, Hongdan; Li, Zhen; Lin, Hui; Wu, Youxing; Du, Qinwen; Wu, Qidi; Cheng, Jun; Liang, Yu; Pan, Yi (Frontiers in Oncology, 2022)
Background and purpose Head and neck cancer (HNC) patients usually present with malnutrition during radiotherapy, leading to loss of skeletal muscle mass (SMM) and poor clinical outcomes. CT has been used in clinical practice for measuring SMM in cancer patients. However, its clinical application for monitoring SMM is limited by the expensive price and high radiation exposure. This study aimed to investigate the feasibility of cone-beam computed tomography (CBCT) for assessing SMM and its changes in HNC patients undergoing radiotherapy. Materials and methods This study was divided into two parts. In part 1 (n = 32), the cross-sectional of skeletal muscle area (SMA) at the third cervical vertebra (C3) based on CBCT and computed tomography (CT) was assessed. In part 2 (n = 30), CT and CBCT were performed, and patients’ weight was measured before and at four different time points during radiotherapy. SMAs at C3 were independently identified by three senior radiation oncologists. The interobserver agreement of SMA on CBCT (SMACBCT) findings was analyzed using the intraclass correlation coefficient (ICC). One-way analysis of variance was used to evaluate the interobserver variability and statistical significance for SMA measurements. CBCT and CT measurement differences and correlations were analyzed using paired sample t-test and Pearson correlation analysis, respectively. The Krouwer variant of the Bland–Altman plot was used to analyze the agreement of SMA measurements between CBCT and CT. A simple linear regression model was used to analyze the relationship of SMA measurements between the two imaging techniques, and the equation was established. A repeated-measures ANOVA was performed to evaluate the effects and interactions between weight loss, SMA loss, and time. Results SMACBCT demonstrated excellent interobserver reliability; no significant difference between SMACBCT and SMA on CT (SMACT) at C3 was observed in all patients. The SMACBCT and SMACT were highly correlated (r = 0.966; 95% confidence interval = 0.955–0.975; p < 0.001). Bland–Altman analysis revealed that SMACBCT was generally higher than SMACT. The predicted SMA value at C3 on CT using CBCT was similar to the actual value. Moreover, significant differences between SMA and weight loss (F =10.99, p = 0.002), groups (weight loss and SMA loss) and times (4 time points) (F = 3.93, p = 0.013), and mean percent loss over time (F = 7.618, p < 0.001) were noted. Conclusion CBCT may be used as an alternative for CT to measure SMA in HNC patients during radiotherapy.